ID23‐2: an automated and high‐performance microfocus beamline for macromolecular crystallography at the ESRF. (22nd February 2022) - Nanao, Max; Basu, Shibom; Zander, Ulrich; Giraud, Thierry; Surr, John; Guijarro, Matias; Lentini, Mario; Felisaz, Franck; Sinoir, Jeremy; Morawe, Christian; Vivo, Amparo; Beteva, Antonia; et al.
Abstract : ID23‐2 is a microfocus synchrotron beamline dedicated to macromolcular crystallography at the ESRF‐EBS. Abstract : ID23‐2 is a fixed‐energy (14.2 keV) microfocus beamline at the European Synchrotron Radiation Facility (ESRF) dedicated to macromolecular crystallography. The optics and sample environment have recently been redesigned and rebuilt to take full advantage of the upgrade of the ESRF to the fourth generation Extremely Brilliant Source (ESRF‐EBS). The upgraded beamline now makes use of two sets of compound refractive lenses and multilayer mirrors to obtain a highly intense (>10 13 photons s −1 ) focused microbeam (minimum size 1.5 µm × 3 µm full width at half‐maximum). The sample environment now includes a FLEX‐HCD sample changer/storage system, as well as a state‐of‐the‐art MD3Up high‐precision multi‐axis diffractometer. Automatic data reduction and analysis are also provided for more advanced protocols such as synchrotron serial crystallographic experiments.